USING SYSTEMIC FUNGICIDES AGAINST OAT FUNGAL DISEASES IN ZHYTOMYR REGION - Derechа O. A.; Gritsyuk, N. V.; Bakalova, A. V.; Kovalchuk, P. C.; Shamray, T. I. (Scientific Progress & Innovations, 2019)
The harmfulness, spreading and developing of stem rust, crown rust and helminthosporiosis in Zhytomyr region was studied. Crown rust turned out to be the most harmful disease: the assimilation processes were upset, the weight of oat grains was reduced, and husk content increased in the affected plants. The grain weight in severe cases decreased by 0.8 g in oats affected with crown rust; under stem rust it was 0.6 g less, and under helminthosporiosis – 0.7 g less as compared with insignificant (5–15 %) levels of the diseases. Therefore, the necessity of applying systemic fungicides both individually in full and in half rates of prepara-tion using arose. At double treatment with Elatus Ria 358 EC 0.5 l/ha; Rex Duo, KS, 0.4 l/ha; Tilt 250 EC, KE, 0.5 l/ha stem rust spreading decreased by 50.1, 47.5, 39.6 % as compared with the control variant. Spraying with tank mixtures resulted in disease reduction. The lowest incidence of the disease was observed at treating with a low dose of Elatus Ria 358 EC 0.3 l/ha + Rex Duo, COP, 0.2 l/ha preparation mixtures. Thus, the spreading and developing of stem rust decreased by 58 % and 31.8 %; crown rust – by 40.0 % and 28.4 %; helmintosporiosis – by 42.5 % and 21.9 % as compared with untreated crops. Applying fungicides favors the formation of a high stable yield with corresponding structural indices. As a result of spraying crops with Elatus Ria 358 EC 0.5 l/ha; Rex Duo, COP, 0.4 l/ha; Slope 250 EC, KE, 0.5 l/ha systemic fungi-cides the grain weight in the parcel increased by 0.20; 0.15; 0.12 g; the weight of 1000 grain increased by 4; 2; 1 g, moreover the number of productive stems increased on 61; 56; 49 pieces per m2 as compared with the control variant. Using systemic fungicides and their tank mixtures increased grain yield by 0.46–1.12 t/ha in comparison with the control variant. Applying tank mixtures (Elatus Ria 358 EC 0.3 l/ha + Tilt 250 EC, CE, 0.3 l/ha) increased the yield by 1.08 t/ha. The highest oat yield was received at crop treatment with the tank mixture of Elatus Ria 358 EC 0.3 l/ha +Rex Duo, KS, 0.3 l/ha, which was 4.42 t/ha, 1.12 t/ha higher than in the control variant. Considering the high harmfulness of crown rust, stem rust and helminthosporiosis we consider it expedient to use the investigated fungicides in production conditions. Under weather conditions favorable for developing and spreading the diseases, two treatments must be conducted.